Question

( sin theta=a cos phi )
( cos theta=operatorname{la} sin phi )
( =left(a^{2}-1right) cot ^{2} phi+left(1-b^{2} cot ^{2} thetaright. )
( =left(a^{2}-1right) frac{cos ^{2} phi}{sin ^{2} phi}+left(1-b^{2}right) frac{cos ^{2} theta}{sin ^{2} theta} )
( =frac{a^{2} cos ^{2} phi-cos ^{2} phi}{sin ^{2} phi}+frac{cos ^{2} theta-b^{2} cos ^{2} theta}{sin ^{2} theta} )
( Rightarrow quad sin theta=a cos phi )
( sin ^{2} theta=a^{2} cos ^{2} phi )
( cos ^{2} phi=frac{sin ^{2} theta}{a^{2}} )
( b sin phi=cos theta )
( b^{2} sin ^{2} phi=cos ^{2} theta )
( sin ^{2} alpha=frac{cos ^{2} theta}{b^{2}} )
( sin frac{cos ^{2} phi}{sin ^{2} phi}=frac{sin ^{2} theta}{a^{2} cos ^{2} theta}=frac{b^{2}}{a^{2}} tan ^{2} theta )
( sin left(a^{2}-1right) frac{b^{2}}{a^{2}} tan ^{2} theta+left(1-b^{2}right) cot ^{2} theta )
( =b^{2} tan ^{2} theta-frac{b^{2}}{a^{2}} tan ^{2} theta+cot ^{2} theta-b^{2} cot ^{2} theta )
Answer is ginderendent of ( theta ), soput ( theta=45^{circ} ) ( =b^{2}-frac{b^{2}}{a^{2}}+1-b^{2}=frac{a^{2}-b^{2}}{a^{2}} sin s(3) )

# ** sine = a cos aihe cos 0 = b sino, -1) cor*(1-b) coto find

Solution